Cartera vencida de la Unidad Educativa Particular Pasionista de la ciudad de Guayaquil en el periodo 2021. - Marmolejo Bajaña, Jordy Damián (2023)
It is the responsibility of the student representatives of the different institutions to make the necessary payments. Private educational institutions in Ecuador keep track of unpaid tuition in overdue portfolios. However, they have yet to make the necessary payments due to a number of factors. As a result, budgets that have been planned to meet the institutions' obligations are forcing the administrative directors of the various institutions to deal with problems. Educational Ctizenship Pasionista cannot take measures to enforce the payment of tuition, such as banning the student from the classroom, due to the student's constitutional right to education. The student cannot be harmed by the parents' carelessness in not paying their tuition, for this reason. In order to determine the overdue portfolio, accounts receivable and liquidity, an analysis was performed, which determined the overdue values in addition to the fact that they do not have collection policies. Regardless of the institution, having sufficient cash available to pay obligations is a critical problem that all companies must constantly address. It should be kept in mind that one of the most crucial resources of an organization is its financial capacity, so it is essential to use this capacity wisely in order to maximize the return on the investment made in the entity.